BLUETOOTH CONTROL SYSTEM ON ELECTRIC WHEELCHAIRS USING VOICE RECOGNITION - Eko Arianto; Bernardinus Sri Widodo; Antonius Hendro Noviyanto; Nugroho Budi Wicaksono; Agatha Mahardika Anugrayuning Jiwatami (Universitas Muhammadiyah Semarang, 2023)
Currently technology is highly developed and supports many new innovations. The most innovation is wireless technology and voice recognition. One of the widely used wireless technology is Bluetooth. By utilizing Bluetooth connectivity and voice recognition applications on smart phones, it can be used to control electronic equipment. In this study, voice recognition applications and Bluetooth connections will be used on smart phones to control electric wheelchairs. This research begins with designing an electric wheelchair. For Bluetooth communication using the HC-05 Bluetooth module. The wheelchair was developed by modifying conventional wheelchairs to become electric. The user or patient will control the wheelchair using his smart phone through the voice recognition application. Commands in the form of voice that will be sent by the smart phone and received by the HC-05 Bluetooth module, then become input for the Arduino microcontroller. The microcontroller will then process the input data and will instruct the motor driver to give instructions to the wheelchair driving motor. The electric wheelchair's voice control system with a Bluetooth connection can work quite well. The Bluetooth connection used in this electric wheelchair voice control system works optimally and well at a distance of <10 meters, the connection starts to drop at a distance of 10 to 23 meters, and the connection is lost when the distance is 30 meters. The results of the voice recognition test on voice commands were successful with an accuracy of 85%. The total test is 100 orders with a total error of 15 orders.